2023
DOI: 10.21203/rs.3.rs-2816538/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the influence of non-ionizing radiation to the morbidity of MRI and ultrasound diagnostics specialists in Kazakhstan

Abstract: The state of health of healthcare practitioners with occupational exposure to a complex of hazards may differ from the state of health of general population and justify the need to develop a number of preventive measures for healthcare practitioners. The purpose of the study was assessment of the prevalence of morbidity among medical specialists (MRI and ultrasound diagnostics). Design: retrospective (2018-2021), nonrandomized. Participants: MRI and ultrasound diagnostics specialists, ophthalmologists (as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The efficacy of preventive programs should also be reflected in the improvement of the level of quality of life of employees [74,75]. In case of a decrease in occupational safety control, there was an increase in trauma and an incidence that may lead to a decrease in the level of quality of life of healthcare practitioners [76][77][78][79][80][81]. A number of authors have found that exposure of medical personnel to EMR may be associated with adverse effects on their cardiovascular system [82].…”
Section: Life Quality Level As An Indicator Of the State Of Healthmentioning
confidence: 99%
“…The efficacy of preventive programs should also be reflected in the improvement of the level of quality of life of employees [74,75]. In case of a decrease in occupational safety control, there was an increase in trauma and an incidence that may lead to a decrease in the level of quality of life of healthcare practitioners [76][77][78][79][80][81]. A number of authors have found that exposure of medical personnel to EMR may be associated with adverse effects on their cardiovascular system [82].…”
Section: Life Quality Level As An Indicator Of the State Of Healthmentioning
confidence: 99%